МӘНАЎИЯТМЫЗДА МИЛЛИЙ ӨЗЛИКТИ АҢЛАЎ - Жамалов, Н.; Ибадуллаев, Б. (SCIENCE and SOCIETY, 2020)
In the article we consider the problem of national identity as an important issue of today, the goal of this problem is aimed at the influence of education on the basis of national identity. We expect only good deeds and actions from youth, but we should not forget, that demanding any achievement from the young generation, we should give them this. If we now educate our young generation in a national spirit, containing comprehensively educational and noble ideas, if we absorb this national spirit in them, we can hope to get good results.
Keywords: self-awareness; national ideology; spirituality; national heritage; national education; ethies; national tradition